Effect of plant extract denture cleansing on heat-cured acrylic denture base resin: An in vitro study - Rizwana Anjum; Sunil V Dhaded; Shalini Joshi; Chandra Shekhar Sajjan; Priyanka Konin; Yavaneetha Reddy (Wolters Kluwer Medknow Publications, 2017)
Aim: Various chemical solutions have been recommended for denture disinfection; however, the immersion effect on the properties of denture base resin may also have effect on strength of the resin material. The purpose of this in vitro study was to compare and evaluate the flexural strength of heat-cure acrylic denture base resin by combination method of denture cleansing and plant extract immersion. Materials and Methods: In this study, ninety specimens of heat-cure acrylic denture base resin material were fabricated with dimensions of 65 mm × 10 mm × 3.3 mm. The specimens were divided into three groups, namely, Group I-III of thirty specimens each and were immersed in distilled water, denture cleanser, and thyme essential oil, respectively. The flexural strength of specimen was evaluated. Results: Natural plant extract showed better flexural strength than immersed in denture cleanser and control group but statistically was not significant. Conclusion: The study concluded that plant extract, namely, thyme essential oil, showed better flexural strength than combination method and can be used as denture cleanser.